Screening of formula for growing stropharia rugosoannulata using tobacco stalks as a substitute and its impact on soil properties for mushroom cultivation (Bangladesh Journal of Botany, 2025)
To explore the feasibility of substituting sawdust with tobacco stalks for cultivating Stropharia rugosoannulata and its impact on soil properties, this study designed cultivation formulas with varying tobacco stalk ratios (0-50%) and analyzed mycelial growth rates, fruiting body agronomic traits, and changes in soil nutrients and enzyme activities. Results showed that the mycelial growth rate first increased and then decreased with a higher tobacco stalk ratio when tobacco stalk ratio was below 50%. T4 (30% tobacco stalks) was optimal with the highest rate (1.69 cm/d), as its tobacco stalk particle size improved mycelium-substrate contact and aeration. D3 (10% tobacco stalks + 90% corn stalks) had the best stipe/cap diameter, individual weight and available K (543.29 mg/kg), while D4 (20% tobacco stalks + 80% corn stalks) showed the highest alkali-hydrolyzed N (118.77 mg/kg) and balanced performance. D6 (100% corn stalks) had the highest available phosphorus content (6.38 mg/kg). Soil enzyme activity analysis indicated that invertase activity peaked in D6 (153.12 mg/g d⁻¹), whereas urease activity was highest in D5 (1.75 μg/g d⁻¹). Correlation analysis showed that the tobacco stalk ratio was extremely positively correlated with the mushroom shape index (r = 0.729**), and urease activity was significantly negatively correlated with fruiting body agronomic traits. In conclusion, T4 promoted mycelial growth, while D3 and D4 aligned soil nutrient improvement with the growth requirements of fruiting bodies, and D4 emerged as the most well-rounded treatment due to its balanced carbon-nitrogen release and favorable fruiting body phenotypic traits.Bangladesh J. Bot. 54(3): 831-840, 2025 (September) Special